2015
DOI: 10.1088/1758-5090/7/1/015012
|View full text |Cite
|
Sign up to set email alerts
|

Maskless fabrication of cell-laden microfluidic chips with localized surface functionalization for the co-culture of cancer cells

Abstract: The utilization of the microfabrication technique to fabricate advanced computing chips has exponentially increased in the last few decades. Needless to say, this fabrication technique offers some unique advantages to develop micro-systems. Though many conventional microfabrication techniques today uses very harsh chemicals, the authors believe that the manipulation of system components and fabrication methods may aid in the utilization of the microfabrication techniques used in fabricating computer chips to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Other chips have been designed to examine drug transport across membranes and the effect of transported drugs on cells cultured on the membrane [47]. Several studies have demonstrated the use of 3D bioprinting to pattern microfluidic channels followed by cells deposited directly into the channels [48][49][50][51], including cocultures of multiple cell types [52]. 3D printing has also been used to generate cell cultures with hepatic sinusoid-like structures within fluid channels [53].…”
Section: Introductionmentioning
confidence: 99%
“…Other chips have been designed to examine drug transport across membranes and the effect of transported drugs on cells cultured on the membrane [47]. Several studies have demonstrated the use of 3D bioprinting to pattern microfluidic channels followed by cells deposited directly into the channels [48][49][50][51], including cocultures of multiple cell types [52]. 3D printing has also been used to generate cell cultures with hepatic sinusoid-like structures within fluid channels [53].…”
Section: Introductionmentioning
confidence: 99%
“…The viability of encapsulated cells is impacted by the processing time of the pre-gel bio-ink preparation and the construct deposition and the sensitivity of different cell types to external stresses. The use of multi-nozzle printheads (e.g., photopolymer, UV, microplasma, bioink, etc) [ 119 ] for co-printing cell-laden hydrogels could decrease the printing time and maximize the cell viability [ 120 , 121 ]. It can be dedicated to printing the tissue constructs and the microfluidic channels simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Extrusion-based printing. Nevertheless, its technique has been applied to fabricate a chip to study cancer cells in a co-cultured microfluidic environment [50]. Inkjet printing has also been applied to a liver-on-a-chip to study drug metabolism and diffusion while showing the ability to utilize multiple cell patterns on a single chip [49].…”
Section: Inkjetmentioning
confidence: 99%